Fault tolerance and protective schemes for DC power distribution - Yap, Heng Goh (2018)
The integration of distributed generation such as renewable energy at the distribution is considered as the better option to cope with the rising demand for electrical energy. The storage system is also introduced to act as an additional power buffer to the power system due to the intermittent supply of energy from the distributed generation. With the addition of these 2 DC energy systems, the DC distribution system can achieve a better system efficiency than the AC system. The DC system can reduce the power conversion stages such as the power factor correction and a rectifier circuit. Of the advantages, the fault protection is the major obstacle for the DC system to move forward. Hence, a research topic is brought out with the major aim is to develop an effective fault tolerance solution to increase the resiliency of the DC distribution system. Complete fault tolerance and protection process with the sequence is:1) fault detection, 2) fault isolation, 3) fault identification, 4) fault recovery. In the DC system, a fast tripping speed of the circuit breaker can reduce the consequences of high fault current sourcing toward the fault point. A T-source circuit breaker is a device for the fault detection and isolation in the DC system. The T-source circuit breaker is a kind of impedance-network based circuit breakers which provide a high-speed breaking capability, and no sensor is required. It also has the benefit of preserves a common ground, zero reflected source current, and provide a low-pass filter behavior. The achievement low output surge fault current is presented. The T-source circuit breaker is modeled in pre-tripping state and post-tripping state. The circuit breaker capacitance of the T-source circuit breaker is selected using the proposed design flow based on the criteria of the current rating, and the load capacitance. The post-tripping model is used as a reference for the output surge fault current to determine the transformer inductance. A manual tripping circuit modification for the protection of SCR device in the T-source circuit breaker is also presented. The selection of the resistor in the modification circuit is based on the current rating. A high accuracy fault identification solution can ease the task of inspection, maintenance, and the repair work. High accuracy can also speed up the restoration service and possesses the merit of less maintenance cost. The probe power unit is a kind of signal injection method. The chosen of the probe power unit as the solution for fault location identification is due to the benefit of single end injection which does not require multipoint measurement, no high data acquisition needed. This method can be 4 used as the fault point tracking in an offline mode whereby the fault current from source has interrupted completely. The logarithm decrement technique is introduced to obtain the damping constant of the damping injection current. The logarithm decrement technique has the advantages of high accuracy, less data reading needed, and fast processing speed. The component selection of the probe power unit with the inductor and capacitor pair value is based on the maximum detectable fault resistance and the peak current deviation tolerance. A wider range of fault resistance can be identified for the fault location identification using the proposed design probe power unit. A modification of the probe power unit circuit associated with the proposed parallel fault identification flow can determine the exact fault segment line with the respective location. This fault identification solution provides information to the fault segment isolation of a complex network such as a meshed network. Fault recovery is a final step of the fault protection process which recovery the non-faulty system back to normal operation. The DC distribution system has various facilities using a different power converter. The standard facilities in the microgrid include the grid interfacing system, the storage system, and the photovoltaic system. A DC circuit breaker is used as the fault interruption device instead of the AC circuit breaker in the DC distribution system. The different placement of DC circuit breaker needs different reconfiguration step than conventional AC circuit breaker for reconnecting the facilities back to the grid. The reconfiguration step is the order of action between the deblocking the power converter and the reclose of DC circuit breaker. The simultaneous connection and sequential connection is compared for the system recovery of facilities. The sequence of reconnecting each facility back to the DC network is demonstrated. Minimum transient of voltage and current profile is chosen as the system recovery step to achieve a stable fault recovery. As above mentioned, the main reason for introducing fault tolerance and protection scheme into the DC system can increase overall system reliability. This protection scheme can prevent a harmful high current triggered in a fault event. In the result, the proposed solution can prevent damaging the non-fault device or facilities attached to the DC system and restore back the facilities into normal mode once the fault point is isolated from the system.